Association between weekend catch-up sleep and chronic kidney disease: insights from NHANES 2017–2020 - Sheng Chen; Ting Zhang; Hongjun Gao; Jianqiang Zhang (Renal Failure)
Objective This study aimed to explore the association between weekend catch-up sleep (WCS) and chronic kidney disease (CKD) in American adults.Methods Utilizing data from the National Health and Nutrition Examination Survey (NHANES) spanning 2017 to 2020, this study encompassed 4,934 individuals aged 20 years and above. We assessed the risk of CKD in relation to WCS. To evaluate CKD risk across various WCS durations, participants were categorized into four groups based on WCS length: < 1 h (reference group), ≥ 1 h and < 2 h, ≥ 2 h and < 3 h, and ≥ 3 h.Results In the fully adjusted multivariate logistic regression model, the odds ratio (OR) of CKD to WCS response was 0.86 (95% CI = 0.61-1.22; p = 0.31). In addition, only CKD was significantly associated with WCS duration between 2-3 h (OR = 0.44, 95% CI = 0.21-0.88, p = 0.03). Subgroup analyses showed stronger negative associations (p < 0.05) for men and women with a WCS of 2-3 h, adults under 60 years of age with a WCS of 2-3 h, those with less than 1 h of catch-up sleep on weekends and a body mass index (BMI) of 25-29.9, those with a BMI of less than 25 or greater than or equal to 30 with a WCS of 2-3 h, and those with less than 7 h of sleep on weekdays and 2-3 h of catch-up sleep on weekends.Conclusion Our findings suggest that when weekday sleep duration is < 7 h, WCS in 2-3 h is strongly associated with a lower prevalence of CKD.